ANALISIS KOMPETENSI DOSEN DAN ALUMNI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Zainal Abidin; Weni Retnowati; Alamsyah Alamsyah (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
This research purposes to identify lecturer competency at Department of Management, waiting time for alumni to get a job, to aligning the education and job fulfill by alumni, and alumni competency after finishing their study at Department of Management in Economics and Business Faculty. The research conducts within nine (9) months in 2018. This is a descriptive research. The object of this researach is every lecture in Department of Management, and alumni that graduate in 2016. The analysis data that used in this research are data reduction, statistic descriptive and other statistic function to gain a conclution. The research data results 95.08% lecturer are described by students as very excellent and others consider as good. As 41.67% lecturer are doctoral graduated, whilst 58.33% are master graduated. The time needed by alumni to get a job data shows that 72.72% alumni’s waiting time is less than 6 months, 15.15% alumni’s waiting time is 7 to 9 months and others need more than 10 months. The aligning between education background and job they take describe as: 8.16% alumni declare it is highly correlated,32.65% said its moderate correlated, whilst 8.16% said there is no correlation between their education and their job.